Decreased risk of cardiovascular disease mortality associated with occasional positive screens following cancer screenings - Yuting Ji; Yu Zhang; Hongyuan Duan; Xiaomin Liu; Yunmeng Zhang; Zhuowei Feng; Jingjing Li; Zeyu Fan; Ya Liu; Yacong Zhang; Lei Yang; Zhangyan Lyu; et al. (Scientific Reports)
Abstract Positive results from cancer screenings, like a cancer diagnosis, can increase the risk of cardiovascular disease (CVD) mortality due to heightened psychological stress. However, positive screening results may also serve as a teachable moment to encourage the adoption of a healthier lifestyle. Consequently, the overall association between positive screenings and CVD mortality risk remains unclear. Based on PLCO data, the risk of CVD mortality associated with the number and types of positive screens was evaluated using Cox regression models among 149,258 eligible participants enrolled between 1993 and 2001. Additional analyses explored these associations stratified by prior CVD history. Exploratory analyses were also conducted to investigate whether positive screens were linked to the potential adoption of a healthier lifestyle. After a median follow-up of 19 years, significantly decreased risk of CVD mortality was observed for individuals with occasional positive screening (≤ 2 positive screens) [adjusted hazard ratio (HR, 95%CIs): 0.931 (0.897–0.968), P < 0.001] compared to the control arm. This effect was particularly notable for flexible sigmoidoscopy [0.842 (0.802–0.884), P < 0.001] and transvaginal ultrasound [0.855 (0.776–0.942), P = 0.002]. However, when the number of positive screens increased to more than two, the reduced risk of CVD mortality became non-significant [0.977 (0.941–1.014), P = 0.220]. Subgroup analyses revealed a greater reduction in CVD mortality risk among participants without a history of CVD [0.917 (0.864–0.973)] compared to those with a history of CVD [0.944 (0.898–0.993)]. Sensitivity analyses excluding screening-detected cancers showed similar association in the overall population [0.933 (0.897–0.970)], as well as in both subgroups with [0.945 (0.898–0.995)] and without previous CVD [0.919 (0.865–0.976)]. Exploratory analyses indicated a significantly higher proportion of any body mass index (BMI) reduction among those with a baseline BMI ≥ 25 kg/m2 who had positive screens compared to the control arm, particularly for individuals with occasional positive screens (48.07% vs. 47.04%, P value = 0.037). Occasional positive cancer screening are associated with reduced risk of CVD mortality, regardless of prior CVD history, cancer diagnosis, and other competitive risks.